Between English and Spanish: A Linguistic Study of Code-switching in Selena Gomez’s Song “Ojos Tristes” - Balqis, Aura Savinka; Gultom, Elfa Salsabila; Rangkuti, Rahmad syah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores how Selena Gomez intentionally switches between English and Spanish in her song